REFLECTION AND ACTION ON TEACHING PRACTICE IN THE EDUCATION OF YOUNG AND ADULT PEOPLE: AN EXPERIENCE LIVED THROUGH DIALOGUE WITH A TEACHER OF CHEMISTRY TEACHING - Kiill, Keila Bossolani; Girotto, Vanessa Cristina; Braz, Natália Mariane; Cordeiro, Márcia Regina (Cadernos de Educação Tecnologia e Sociedade, 2019)
This article is the result of a master's research carried out jointly with educators, learners and people involved in the education of young people and adults in general, and with the teaching of chemistry. Through this research, we seek to understand the process of formation of an educator of young people and adults, his uncertainties, limitations and the importance of rethinking actions and attitudes that happen every day and each experience lived while teaching for this specific teaching modality. Developed from the communicative methodology of research, this research had communicative observations, communicative life reports and discussion groups as its main instruments of data collection and involved an intersubjective analysis of the information collected. The results showed, for the most part, a teaching based on the mechanical memorization of chemical contents, the result of an initial training deficient that was commented by the teacher himself; and classes with content facilitated, summarized and focused more on the difficulties to learn than on the potentialities. Also transforming elements were observed, emphasizing the improvement of both academic learning and social interaction.